Effect of different concentrations of ZnSO4 on Pistacia atlantica plantlets growth under semi-controlled conditions - Daoudi S.; Hamada O.; Doghbage A.; Belhadj S. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The effect of ZnSO4 stress on some morphological, physiological and biochemical parameters of Pistacia atlantica plantlets was studied under semi-controlled conditions. The plants were grown in pots and irrigated with distilled water for 30 days. Then, the plantlets were treated with 0, 0.01, 0.1 and 1 mmol of ZnSO4 for 18 days. The application of these concentrations caused stress on the young Pistacia atlantica plantlets by reducing the growth of morphological parameters. The amount of free proline in shoots and roots grows significantly with the concentration in the medium of ZnSO4 for all the treatments. On the other hand, no significant difference in relative water content was noted. These results are indicating that P. atlantica can be used in phytoremediation because of its rusticity and resistance to stress caused by Zinc.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)